How to Increase E-Repurchase of E-Pay Consumers in Purwokerto - Monica Rosiana; Dwita Aprillia Floresti (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
The purpose of this study is to explain the effect of perceived usefulness, perceived ease of use, perceived risk on e-repurchase using e-pay. Structural Equation Modeling (SEM) was used to test the empirical model. The number of samples in this study was 114 e-pay users in Purwokerto. The results indicate that perceived usefulness and perceived ease of use have a positive effect on e-repurchase. In addition, researchers can also prove that perceived risk has a negative effect on e-repurchase.